The Influence of Perceived Ease of Use, Benefits, and Financial Literacy on Digital Banking Adoption with Trust as a Mediating Variable - Putri Yulia Salsabilla; Feri Dwi Riyanto; Irmayanti Hasan (Universitas Negeri Padang, 2026)
Despite the high digital engagement of the younger generation, a research gap exists regarding how psychological perceptions and financial knowledge interact to drive actual banking behavior in specific regional contexts. This study aims to analyze the effect of perceived ease of use, perceived usefulness, and financial literacy on digital banking usage, with trust as a mediating variable among Generation Z students in Malang. This research employs a quantitative approach with an associative research design. Data were gathered via a 5-point Likert-scale survey administered to 100 participants from five prominent universities in Malang. Analysis employed Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS software. The results indicate that perceived ease of transaction, usefulness, and financial literacy have a positive and significant effect on digital banking adoption. Furthermore, these variables also have a considerably positive influence on trust. Trust is confirmed to have a substantial positive impact on digital banking usage and significantly mediates the relationship between perceived ease of transaction, perceived benefits, financial literacy, and use of digital banking. In summary, the results indicate that perceived ease of use, benefits, and financial literacy either directly or via mediating power of trust as key drivers in promoting digital banking uptake among Generation Z students.